2021
DOI: 10.1159/000518380
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Neurovascular Structural Changes in Optical Coherence Tomography and the Relationship between These Changes and White Matter Hyperintensities in Patients with Migraine

Abstract: <b><i>Introduction:</i></b> This study aimed to reveal whether retinal nerve fiber layer (RNFL), ganglion cell layer (GCL) inner plexiform layer, and choroidal layer (CL) thicknesses differed in patients with migraine. Optical coherence tomography (OCT) was used to measure these neurovascular structural changes and determine the relationship between these structures and cranial white matter hyperintensities (WMHs). <b><i>Methods:</i></b> This retrospective compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…OCT has been used to research neuroinflammatory and neurodegenerative diseases, such as multiple sclerosis, neuromyelitis optica spectrum disorder, Alzheimer's disease and Parkinson's disease [11,[13][14][15], and may aid our understanding of the pathogenesis and pathophysiology of CSVD. Indeed, the PRNFL thickness was significantly reduced in CADASIL patients and CSVD patients with severe WMHs [16], although undetermined correlations have also been reported [17] and additional research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…OCT has been used to research neuroinflammatory and neurodegenerative diseases, such as multiple sclerosis, neuromyelitis optica spectrum disorder, Alzheimer's disease and Parkinson's disease [11,[13][14][15], and may aid our understanding of the pathogenesis and pathophysiology of CSVD. Indeed, the PRNFL thickness was significantly reduced in CADASIL patients and CSVD patients with severe WMHs [16], although undetermined correlations have also been reported [17] and additional research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…We found 35 studies examining specifically the RNFL in migraineurs and found that studies have inconsistently shown that migraineurs have thinner RNFL than controls ( Cunha et al, 2008 ; Costello, 2009 ; Gipponi et al, 2013 ; Sorkhabi et al, 2013 ; Ekinci et al, 2014 ; Demircan et al, 2015 ; Yülek et al, 2015 ; Acer et al, 2016 ; Demirci et al, 2016 ; Feng et al, 2016 ; Verroiopoulos et al, 2016 ; Ergiyit, 2017 ; Reggio et al, 2017 ; Tunç et al, 2017 ; Abdellatif and Fouad, 2018 ; Tak et al, 2018 ; Bing et al, 2019 ; Ulusoy et al, 2019 ; You et al, 2019 ; Sirakaya et al, 2020 ; Yener and Yılmaz, 2020 ; Altunisik and Oren, 2021 ; Kanar et al, 2021 ; Panicker et al, 2021 ; Temel et al, 2021 ; Yurtoğulları et al, 2021 ), generally ipsilateral to the usual side of headache ( Martinez et al, 2008 ; Gunes et al, 2016 ; Khosravi et al, 2018 ). Lin et al examined 26 studies and also found thinner mean RNFL in migraineurs than in controls, especially in the superior and inferior eye quadrants ( Lin et al, 2021 ).…”
Section: Retinamentioning
confidence: 95%
“…Nineteen studies showed ganglion cell complex thinning in migraineurs (Güler et al, 2020). Compared to controls, both aura and non-aura migraineurs had thinner GCL (Ekinci et al, 2014;Reggio et al, 2017;Abdellatif and Fouad, 2018;Altunisik and Oren, 2021;Yurtoğulları et al, 2021), where chronicity and severity yielded greater GCL reduction (Abdellatif and Fouad, 2018). The presence of WMH did not influence this effect (Altunisik and Oren, 2021).…”
Section: Ganglion Cell Layer (Gcl)mentioning
confidence: 99%
See 2 more Smart Citations